2017
DOI: 10.1515/bnm-2016-0015
|View full text |Cite
|
Sign up to set email alerts
|

Biofunctionalization of surfaces using polyelectrolyte multilayers

Abstract: Abstract:Biomaterials play a central role in modern strategies in regenerative medicine and tissue engineering to restore the structure and function of damaged or dysfunctional tissue and to direct cellular behavior. Both biologically derived and synthetic materials have been extensively explored in this context. However, most materials when implanted into living tissue initiate a host response. Modern implant design therefore aims to improve implant integration while avoiding chronic inflammation and foreign … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 86 publications
0
20
0
Order By: Relevance
“…Antiadhesive properties depend on surface morphology or mechanical properties, in turn bactericidal effect is maintained by the presence of an active antibacterial component. 17,52 Our results suggested that all LbL coatings have shown anti- LbL multilayers. The bactericidal activity of these films could be associated with the presence of silver nanoparticles in the upper layer.…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations
“…Antiadhesive properties depend on surface morphology or mechanical properties, in turn bactericidal effect is maintained by the presence of an active antibacterial component. 17,52 Our results suggested that all LbL coatings have shown anti- LbL multilayers. The bactericidal activity of these films could be associated with the presence of silver nanoparticles in the upper layer.…”
Section: Discussionmentioning
confidence: 61%
“…The bacterial adhesion to the different substrates is dependent on the component composition and their physicochemical properties, for instance, stiffness, hydrophilicity, topography, and so on. 1,17 Antibacterial activity of LbL coatings can be associated with their antiadhesive and bactericidal properties. Antiadhesive properties depend on surface morphology or mechanical properties, in turn bactericidal effect is maintained by the presence of an active antibacterial component.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Within the current issue, Hartmann and Krastev [1] outline specific strategies using polyelectrolyte multilayers to modulate these interactions between biomaterial surfaces and biological systems. Biofunctionalization is one particular form of surface modification involving the immobilization of biomolecules as proteins, peptides and polysaccharides or bioactive drugs with the same purpose.…”
Section: Doi: 101515/bnm-2017-0007mentioning
confidence: 99%